The Effect of Pliometric Training Knee Tuck Jump and Jump To Box on the Jump Height of Volleyball Athletes - M. Dandy Aryadi; Ayadi, M. Dandy (Universitas Negeri Semarang, 2024)
The purpose of this study was conducted to determine the effect of plyometric knee tuck jump and Jump to box training on the jump height of volleyball athletes. This study uses an experimental method with a two group pretest posttest design. The population in this study were 35 PBV.Kapila Tanjungpinang male volleyball athletes using probability sampling technique in determining the number of samples so that a sample of 30 people was obtained. The instrument in this study used the vertical jump test. The data analysis technique uses a hypothesis test (t-test) to determine the difference in the effect of pretest and posttest. The results of the research showed 1) In the knee tuck jump training group on jump height has a significant effect (P < 0.05). This can be proven that the average value of the post test is higher than the average value of the pre test or (μA1 37.20 < μA2 45.87) with a difference of 8.65. 2) In the jump to box training group on jump height has a significant effect (P < 0.05). This can be proven that the average value of the post test is higher than the average value of the pre test or (μA1 35.20 < μA2 55.87) with a difference of 20.67. 3). In the knee tuck jump and jump to box training groups on jump height there is a significant difference in influence (P < 0.05). This can be proven that the average value of the post test of the jump to box training group obtained an average value of 55.87 is greater than the average value of the knee tuck jump training group 45.87 (μB2 55.87 ≥ μA2 45.87) with a difference of 10. Based on the research findings, it can be concluded that knee tuck jump training and jump to box training, have a significant and positive effect on leg muscle strength in PBV.Kapila Tanjungpinang volleyball athletes. Although both show a significant positive effect, jump to box training is more effective in increasing leg muscle strength compared to knee tuck jump training.